Carotenoid production by Haloferax mediterranei using starch residues from the candy industry as a carbon source - Micaela Giani; Carmen Pire; Rosa María Martínez-Espinosa (Current Research in Biotechnology)
Carotenoids are pigments attracting the attention of several industries due to their antioxidant, biological and coloring properties. Low-cost substrates, such as agro-industrial wastes, are being investigated as a viable option to reduce microbial production costs in processes in which microorganisms such as haloarchaea are used as cell factories to produce marketed compounds like carotenoids. They can grow on various agro-industrial wastes and produce the C50 carotenoid bacterioruberin (BR), which is an extraordinary antioxidant compound with anticancer properties. In this study, the haloarchaeon Haloferax mediterranei is grown in the presence of starch residues from the candy industry to induce the production of carotenoids. Cells grew successfully with this industrial waste (max. O.D. 600 nm = 27.75 ± 0.09). Biomass production increased in the presence of higher quantities of starch up to 17.3 ± 0.2 mg/ml of cell culture. The maximum BR concentration was 97.39 ± 1.86 µg/ml. The total amount of BRs synthesized increased when cells grew with increasing concentrations of the industrial starch. The relative percentages of all-trans-BR, 5-cis-BR and a double isomeric BR rose, whereas 9-cis-BR and 13-cis-BR levels decreased.Herein, haloarchaeal growth and carotenoid production can be enhanced using industrial waste products as the starch residues selected for this experiment which were provided by a candy company.